She poured out her heart [large type] - Thompson, Jean, 1950- (Thorndike Press, 2016)
Tracing the complicated friendship of two very different women who meet in college, She Poured Out Her Heart is a novel of remarkable psychological suspense as well as a finely wrought, haunting story of female friendship and deception and the distance in between.